2017
DOI: 10.1038/srep38982
|View full text |Cite
|
Sign up to set email alerts
|

Integrated crop management practices for maximizing grain yield of double-season rice crop

Abstract: Information on maximum grain yield and its attributes are limited for double-season rice crop grown under the subtropical environment. This study was conducted to examine key characteristics associated with high yielding double-season rice crop through a comparison between an integrated crop management (ICM) and farmers’ practice (FP). Field experiments were conducted in the early and late seasons in the subtropical environment of Wuxue County, Hubei Province, China in 2013 and 2014. On average, grain yield in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 25 publications
5
24
0
2
Order By: Relevance
“…Our results confirm the findings of Wang et al. (), where enhanced yield through improved agronomic practices was generally realized by an increase in panicle numbers. Our results indicate that the multiplier effect from the use of multiple cultivation techniques (e.g., SHY) can improve grain yield.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results confirm the findings of Wang et al. (), where enhanced yield through improved agronomic practices was generally realized by an increase in panicle numbers. Our results indicate that the multiplier effect from the use of multiple cultivation techniques (e.g., SHY) can improve grain yield.…”
Section: Discussionsupporting
confidence: 92%
“…Wang et al. () showed that integrated agronomic practices can achieve higher yields and use resources more efficiently than single‐factor agronomic practices. Under integrated agronomic practices, rice yield increased by more than 15%, and the agronomic utilization rate of N fertilizer increased by more than 50%, which shows far greater increases than the gains achieved from using single cultivation techniques (Peng et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…(), who stated that increasing planting density with a reduction in basal N rate and constant N top‐dressing at panicle initiation might benefit rice production and lead to a high grain yield. Improvement in nutrient management (such as those in Qin et al., ; Wang et al., ) supported higher crop growth rate (CGR) throughout the growing season and higher N uptake as well when compared with farming practices which would increase the risk of nutrient losses and cause environmental concerns. Crop growth rate during the vegetative and grain‐filling stages, AE, and PEP increased with seedling density increasing (Figure , ).…”
Section: Discussionmentioning
confidence: 99%
“…This results were found because all favourable conditions received the field ICM practice. This result was supported by Wang et al (2017). The interaction of variety and different management practices had no significant influence on yield and yield components.…”
Section: Resultsmentioning
confidence: 56%